Letter from R.E. Preston to Margaret M. Booth, March 10, 1888 - Preston, Robert E., 1836–1911 (1888)
Letter from Robert E. Preston (1836-1911), of the United States Mint Bureau, to Margaret M. Booth, wife of James Curtis Booth (1810-1888), informing her that progress is being made in Washington on the bill for James' relief.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Martinez Cardeza, Margaret; Preston, Robert E., 1836–1911; United States Mint; Mint of the United States